2003
DOI: 10.1159/000074567
|View full text |Cite
|
Sign up to set email alerts
|

Role of Retinal Detachment Subretinal Fluid on Extracellular Matrix Metabolism

Abstract: Purpose: To examine the in vitro effects of subretinal fluid (SRF) from patients with retinal detachment on extracellular matrix turnover. Methods: Matrix metalloproteinase (MMP) activity was explored by radiolabeled substrate degradation and zymography. Human lung fibroblasts were used to analyze SRF effects on collagen synthesis and cell proliferation. Transforming growth factor-β2 (TGF-β2) concentration was determined in SRF samples by a quantitative sandwich enzyme immunoassay. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
0
15
0
3
Order By: Relevance
“…MMPs and/or TIMP−1 were each differentially expressed with respect to extent and duration of RRD and stage of PVR. The finding of this study that the expression of active gelatinases coincides with grade C and the significant correlation between PVR grade and MMP−2 levels in association with the fact that SRF from RRD has been found to stimulate fibroblast proliferation and collagen synthesis may imply that both gelatinases are involved in the retinal detachment process and PVR [14,18].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…MMPs and/or TIMP−1 were each differentially expressed with respect to extent and duration of RRD and stage of PVR. The finding of this study that the expression of active gelatinases coincides with grade C and the significant correlation between PVR grade and MMP−2 levels in association with the fact that SRF from RRD has been found to stimulate fibroblast proliferation and collagen synthesis may imply that both gelatinases are involved in the retinal detachment process and PVR [14,18].…”
Section: Discussionmentioning
confidence: 86%
“…MMPs expressed mainly at the onset of RRD (such as collagenases and stromelysin) may be associated with wound initiation, matrix degradation and oedema [37]. On the other hand, MMPs expressed throughout RRD development (such as active gelatinases) may be associated with wound-healing processes, including deposition of newly formed fibrous tissue in the inner and outer surfaces of the neural retina [4], angiogenesis [20] and excessive proliferation [14]. In this respect, it has been proposed that once the period of peak MMP activity is established, a possible therapeutic intervention may be feasible with the use of specific naturally occurring or synthetic MMP inhibitors [12,30].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown the correlation of MMP-2 and MMP-9 to be involved in retinal diseases [2,9,12,[40][41][42][43][44]. The increase in MMP-9 mRNA expression peaked at day 2 after LPC in the chicken retina (fivefold of control, data not shown).…”
Section: Discussionmentioning
confidence: 78%
“…Breakdown of the blood-retinal barrier following RRD results in the leakage of blood, which may promote an inflammatory reaction and the proliferation of retinal glial and RPE cells. 24,25 In previous studies, various factors involved in the inflammation process, such as gelatinase activity, 26,27 connective tissue growth factor, 28 pigment-epithelium-derived factor, 29 IL-6, 30 s-100, 31 and TGF-b2 25 have been reported to be present in SRF. In our study, ARPE-19 cells cocultured with SRF showed elevated expression of ICAM-1 in vitro.…”
Section: Resultsmentioning
confidence: 99%